1983
DOI: 10.1080/00140138308963376
|View full text |Cite
|
Sign up to set email alerts
|

Waiting in the wings Apprehension, public speaking and performance

Abstract: Inexperienced speakers were tested shortly before they presented colloquium papers at a public forum. Increases in anxiety and arousal were found using subjective and ECG measures. Performance deteriorated in digit span and verbal fluency but not in logical reasoning, tick length or the Stroop test. However, degree ofdecrement was small and rate of accumulatingdata slow, suggesting this is not an ideal situation for studying the effects of apprehension on performance, IntroductionThe question of how fear and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 24 publications
2
4
1
Order By: Relevance
“…Our results hence replicate the various observations of an effect of anxiety on span (e.g. Moldawsky andMoldawsky 1952, Idzikowski andBaddeley 1983 b).…”
Section: Performance Measuressupporting
confidence: 90%
See 2 more Smart Citations
“…Our results hence replicate the various observations of an effect of anxiety on span (e.g. Moldawsky andMoldawsky 1952, Idzikowski andBaddeley 1983 b).…”
Section: Performance Measuressupporting
confidence: 90%
“…In both this study and our previous experiment using public speaking (Idzikowski and Baddeley 1983 b), decrements in cognitive performance were observed, but in both cases the magnitude of these effects was far from large. There are a number of possible reasons for this.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Porhola (1999), for example, reported that speakers with moderately elevated heart rates demonstrated high levels of public speaking competence while those with precipitously faster heart rates gave presentations of much poorer quality. Excessive physiological arousal contributes to the inefficient use of memory resources (Idzikowski & Baddeley, 1983), and diminishes the efficiency of cognitive processing during performance (Mendl, 1999). Consequently, excessive arousal has been associated with disruptions and inhibited behavior during public speaking (Beatty, Dobos, Balfantz, & Kuwabara, 1991;Freeman, Sawyer, & Behnke, 1997).…”
mentioning
confidence: 99%
“…The situation of giving testimony is a high anxiety condition. In their study of apprehension in public speaking, Idzikowski and Baddeley (1983) found that subjects were more tense and troubled and showed an increase in heart rate before speaking. It is therefore important to understand whether this apprehension is exacerbated by waiting for a time before testifying and, if it is, whether this is noticed and interpreted by the juror in a manner that could be detrimental to the presentation of the facts of the case.…”
Section: Variables That Influence Time Judgmentsmentioning
confidence: 99%